Language, teaching, and pedagogy for refugee education - Sengupta, Enakshi; Blessinger, Patrick (Emerald Publishing Limited, 2019)
This volume is focused on the core areas of imparting education to the refugee population and highlights the recent developments intended to meet an urgent need: that of the refugees who have no or very little previous schooling and who are in need of both language learning and furthering their studies for higher education. This book is designed to provide recognition to those who are working relentlessly towards imparting education to vulnerable people and giving them the tools they need to help withstand and recover from the effects of conflict and displacement. The chapters in this book speaks about some exemplary work done by individuals and institutions from Africa to Germany.
Includes indexes.
Keywords: Refugees -- Education (Higher); Language and languages -- Study and teaching.; Education / Bilingual Education.; Refugees & political asylum.; elektronické knihy; electronic books